Professional Competences and Class of Behaviors Required in the Work of Lodging Facilities - Lamonato, Creici; Presser, Nadi Helena (Revista Turismo em Análise, 2015)
This research outlines the professional competences required for the execution of tasks for those who work in lodging facilities. The research was carried out through the decomposition of the class of behaviors which a given position in the area demands. Descriptive research that collected data from 52 job vacancies advertised in five sites announcing national vacancies: Sine, Catho, Indeed, Pense Emprego, and Manager. Data was classified and analyzed according to the variables presented in the advertisings for the jobs studied. As main results the study identified ten classes of behaviors: communicate with clients, relate to clients, proactivity, organize activities, act with agility concentrate on the solutions of problems, work in a team, plan actions, carry out activities technically and lead focusing on results. These ten classes of behavior were translated in various classes of intermediary behaviors of positions. Regarding levels of formal education, the study found that 73% of the vacancies in the operational and managerial level hire professionals who have at least secondary school level or higher education. Only six vacancies requiring higher education demanded for a degree in the area of hotel, tourism and gastronomy. The study also showed that only 27% of the vacancies required professionals who mastered foreign languages.